Analisis Variasi Kecepatan Spindel Dan Pemakanan Proses Bubut Terhadap Kekasaran Permukaan Benda Kerja Pada Baja AISI 1018 Menggunakan Pahat HSS - Gabriel Armando Situmeang; Bobie Suhendra (Peneliti.net, 2023)
In manufacturing, conventional lathes are known to be used to make component. The purpose study was to determine the level surface roughness using workpiece surface roughness measuring device, name the Roughness tester. Arithmetic average parameters, and determine the effect variations in rotational speed and feed motion on the level of surface roughness in the low carbon steel turning process of AISI 1018 type. This study uses an experimental method involving several variables, the independent variable is the independent variable (X) and production variable (Y). Based on the results turning, 6 specimens of test specimens were obtained for roughness testing with variations in speed of 380 Rpm, 840 Rpm and food 1 mm, 1.5 mm, 2 mm. The influence spindle rotation speed roughness The AISI 1018 steel surface shows decreasing trend in roughness value. This due to the increase in spindle rotation speed will reduce the vibrations occur during the turning process. At spindle rotation speed 380 rpm the lowest surface roughness value Ra 0.9699µm and at a spindle rotation speed of 840 rpm the lowest surface roughness value is Ra 0.4455µm so that’s a variable speed 840 rpm with food depth of 1 mm, the surface turning method works well